FINANCIAL PRIVILEGES OF MINORITIES IN AN ISLAMIC STATE - Dr. Amir Hayat; Dr. Syeda Sadia; Dr. Sumera Rabia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Islam is a religion that stands for justice and peace for all humanity. It advocates for the rights to all members of the society regardless of their religious faith. To participate in economic activities is vital for the sustenance of individuals. An Islamic state does provide opportunities to participate in economic activities to earn respectable livelihood and minorities are no exception. The current paper is focused on the elaboration of economic rights of minorities in an Islamic state. The paper is built on the argumentation based on the basic sources of Islam and from the early Islamic history. Moreover, all the economic rights of minorities in Islam provided in Islamic teachings are seen in special perspective of current situation of minorities in Pakistan and way forward is suggested. The turbulent and vibrant environment of Pakistan has opened new avenues to study rights of minorities. The paper is constructed on the extensive review of basic sources of Islam to find Islamic principles of economic rights of minorities in the verses of the glorious Quran, traditions of the Holy Prophet, and current literature available on Islamic principles minority rights. The current research is aimed at highlighting economic rights of minorities in Islam to bridge the gap between Muslims and minorities. The conclusions shall help in creating inter-faith harmony in Pakistan.